Correction: Fabrication of asymmetrical diffusion dialysis membranes for rapid acid recovery with high purity. Issue 21 (12th May 2016) - Lin, Xiaocheng; Shamsaei, Ezzatollah; Kong, Biao; Liu, Jefferson Zhe; Xu, Tongwen; Easton, Christopher D.; Wang, Huanting
Abstract : Correction for 'Fabrication of asymmetrical diffusion dialysis membranes for rapid acid recovery with high purity' by Xiaocheng Lin et al., J. Mater. Chem. A, 2015, 3, 24000–24007.